2002
DOI: 10.1051/0004-6361:20020986
|View full text |Cite
|
Sign up to set email alerts
|

Abundances of Planetary Nebula NGC 5315

Abstract: Abstract. The ISO and IUE spectra of the elliptical nebula NGC 5315 is presented. These spectra are combined with the spectra in the visual wavelength region to obtain a complete, extinction corrected, spectrum. The chemical composition of the nebulae is then calculated and compared to previous determinations. The HST NICMOS observations of the nebula in 3 emission lines are also presented. These observations are used to determine the helium abundance as a function of position in the nebula. A discussion is gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 19 publications
9
65
0
Order By: Relevance
“…2). This has previously been detected for NGC 7027 (Bernard Salas et al 2001), NGC 6302 (Pottasch & Beintema 1999) and NGC 6537 (Pottasch et al 2000). A simple picture of a planetary nebula is that close to the central star there exist more high energy UV photons than in the outer regions.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…2). This has previously been detected for NGC 7027 (Bernard Salas et al 2001), NGC 6302 (Pottasch & Beintema 1999) and NGC 6537 (Pottasch et al 2000). A simple picture of a planetary nebula is that close to the central star there exist more high energy UV photons than in the outer regions.…”
Section: Discussionmentioning
confidence: 56%
“…This comparison is shown in Table 1. The SWS and IRAS fluxes (Pottasch et al 2000) are shown in Cols. 4 and 5. In the last column the scale factor to reproduce the IRAS measurements (basically F iras /F sws ) is given.…”
Section: Aperture Correctionsmentioning
confidence: 99%
“…The reasons for this have been discussed in earlier studies (e.g. see Pottasch & Beintema 1999; Pottasch et al 2000Pottasch et al , 2001Bernard Salas et al 2001), and can be summarized as follows.…”
Section: Introductionmentioning
confidence: 85%
“…Pottasch 2003, private communication). When the results calculated from ISO data are compared to other recent abundance determinations, large errors (sometimes of factors two to three) are found (see Pottasch et al 2000 for an example).…”
Section: The Observationsmentioning
confidence: 99%
“…Pottasch 2003, private communication). These abundances will be much more accurate than just using visual data alone because infrared data do not depend on electron temperature, the number of ions observed may double, which reduces the uncertainty in the ionisation correction factor substantially and extinction corrections may be determined in an independent way (Pottasch, Beintema, & Feibelman 2000). Indeed, for the cases of neon, oxygen and argon, ionisation correction factors are no longer needed (S.R.…”
Section: The Observationsmentioning
confidence: 99%